2011
DOI: 10.5194/astra-7-315-2011
|View full text |Cite
|
Sign up to set email alerts
|

Forbush decreases – clouds relation in the neutron monitor era

Abstract: The proposed influence of cosmic rays on cloud formation is tested for the effect of sudden intensity changes of CR (Forbush decreases) on cloudiness. An attempt is made to widen the investigated period covered by satellite observation of cloudiness. As an indicator of cloud cover, the diurnal temperature range (DTR - a quantity anticorrelated with cloudiness) is used. The superposed epoch analysis on a set of isolated Forbush decreases is conducted and the results for a region of Europe are presented. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 10 publications
3
48
4
Order By: Relevance
“…Kristjánsson et al [] and Todd and Kniveton [] found some response in cloud satellite data, while Pudovkin and Veretenenko [], Harrison and Stephenson [], and Harrison and Ambaum [] found a response based on surface observations. A signal in middle‐ and high‐level clouds has been reported by Rohs et al [], and Dragić et al [] found a signal by using the diurnal temperature range as a cloud proxy, which allowed them to extend the data range farther back than the onset of satellite measurements.…”
Section: Introductionmentioning
confidence: 87%
“…Kristjánsson et al [] and Todd and Kniveton [] found some response in cloud satellite data, while Pudovkin and Veretenenko [], Harrison and Stephenson [], and Harrison and Ambaum [] found a response based on surface observations. A signal in middle‐ and high‐level clouds has been reported by Rohs et al [], and Dragić et al [] found a signal by using the diurnal temperature range as a cloud proxy, which allowed them to extend the data range farther back than the onset of satellite measurements.…”
Section: Introductionmentioning
confidence: 87%
“…Onehour time series of the cosmic ray muon intensity at the ground level are checked for correlation with European neutron monitors ( NM ), with emphasis on occasional extreme solar events, e.g. Forbush decreases (FD ) in order to investigate claims of influence of cosmic-rays on cloud formation and climate [8,9] In some specific time periods, like during the FD in March 2012, we showed that our muon measurement system has sensitivity comparable to European neutron monitors in this period, but still not as efficient as NM with better geographical position (at high altitude), e.g. Jungfraujoch in the Swiss Alps.These results are presented at Fig.…”
Section: Simulation and Resultsmentioning
confidence: 99%
“…For consistency, we have used the same 189 European region meteorological stations as listed in the on-line supplementary material of Dragić et al (2011). An example of the daily values of DTR from Dnipropetrovśk station (Ukraine), is shown in figure 1(a).…”
Section: Meteorological Station Datamentioning
confidence: 99%
“…It has been proposed by Dragić et al (2011Dragić et al ( , 2013) that a long-debated link between solar activity and terrestrial cloud properties may be reliably detected by applying composite analysis techniques to observations of the diurnal temperature range (DTR-a quantity defined as the difference between observed daily minimum and maximum surface air temperatures). Dai et al (1999) have shown that the DTR can be used as a proxy for cloud cover, and so detections of significant DTR changes corresponding to solar variability (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation